2019
DOI: 10.1139/cjpp-2018-0674
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 supplementation ameliorates ovariectomy-induced cardiac apoptotic and structural changes in adult albino rats

Abstract: The effect of vitamin D on cardiac dysfunction after menopause is still under investigation. Therefore, we investigated the effect of vitamin D3 on cardiac apoptotic and structural changes in ovariectomized rats. Forty adult female albino rats were divided into 4 equal groups: sham rats, sham rats treated with vitamin D3, ovariectomized rats, and ovariectomized rats treated with vitamin D3 (500 IU/kg per day for 6 weeks, orally). Body mass, blood pressure, heart rate, and whole heart mass (WHM) were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Hajar et al 38 found that 50,000 IU calcitriol supplementation every 2 weeks for 4 months in participants with premenstrual syndrome significantly decreased serum levels of interleukin (IL)‐10 and IL‐12, whereas T‐AOC significantly increased. In rats with OVX‐induced cardiac dysfunction, after 500 IU/kg per day calcitriol supplementation for 6 weeks, the total antioxidant capacity increased and cardiac Fas and FasL apoptosis‐related protein expressions decreased 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hajar et al 38 found that 50,000 IU calcitriol supplementation every 2 weeks for 4 months in participants with premenstrual syndrome significantly decreased serum levels of interleukin (IL)‐10 and IL‐12, whereas T‐AOC significantly increased. In rats with OVX‐induced cardiac dysfunction, after 500 IU/kg per day calcitriol supplementation for 6 weeks, the total antioxidant capacity increased and cardiac Fas and FasL apoptosis‐related protein expressions decreased 39 …”
Section: Discussionmentioning
confidence: 99%
“…(E) The quantitative results of cell apoptosis (n = 3). *p < 0.05 compared with the control group; # p < 0.05. interleukin (IL)-10 and IL-12, whereas T-AOC significantly increased.In rats with OVX-induced cardiac dysfunction, after 500 IU/kg per day calcitriol supplementation for 6 weeks, the total antioxidant capacity increased and cardiac Fas and FasL apoptosis-related protein expressions decreased 39. Vitamin D also plays a role in immunomodulation, antiinflammation and antiaging.…”
mentioning
confidence: 99%
“…Several studies have reported the cardioprotective effect of vitamin D in different experimental models at both low and high doses (500 IU/kg/day to 60.000 IU/day). 12 , 13 , 14 Thus, in this study, we aimed to investigate the possible cardioprotective effect of vitamin D3 in hyperthyroid-induced cardiomyopathy rat model. Also, several studies had shown the role of vitamin D3 as adjuvant therapy in management of type 2 diabetes mellitus, melanoma and respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…for 4 weeks daily, and received the vitamin D3 (cholecalciferol) simultaneously at a dose of 500 IU/kg, dissolved in corn oil orally by gavage daily for the same duration of 4 weeks, according to previous protocols. 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation